2001
DOI: 10.1021/la010672i
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of High-Density Poly(Ethylene Glycol) Monolayers on Si(111)

Abstract: A strategy has been developed for the grafting of poly(ethylene glycol) (PEG) monolayers onto the atomically flat Si(111) surface. This process involves the direct interaction of the HO-functional group on PEG with a chlorine-terminated silicon surface. The resulting monolayers show exceptional flatness, with mean roughness on the angstrom scale. Film thickness is determined by ellipsometry, X-ray photoelectron spectroscopy, and atomic force microscopy. Results for different molecular weights reveal that the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 20 publications
10
100
1
Order By: Relevance
“…[22] The limited success of physisorption and covalent grafting (the ''grafting to'' approach) in reducing protein adsorption has been attributed to the low surface density of PEG chains on the surface (<4 mg cm À2 ), [23] because of the excluded-volume effect. [24,25] A breakthrough in the development of protein-resistant materials came from the work of Prime and Whitesides, who showed that self-assembled monolayers (SAMs) of OEG-terminated alkanethiols (OEG-SH) confer protein resistance to gold, as determined by SPR. [16] Although OEG-SH SAMs on gold exhibited…”
Section: à2mentioning
confidence: 99%
“…[22] The limited success of physisorption and covalent grafting (the ''grafting to'' approach) in reducing protein adsorption has been attributed to the low surface density of PEG chains on the surface (<4 mg cm À2 ), [23] because of the excluded-volume effect. [24,25] A breakthrough in the development of protein-resistant materials came from the work of Prime and Whitesides, who showed that self-assembled monolayers (SAMs) of OEG-terminated alkanethiols (OEG-SH) confer protein resistance to gold, as determined by SPR. [16] Although OEG-SH SAMs on gold exhibited…”
Section: à2mentioning
confidence: 99%
“…The solubility of salts in ethylene glycol (EG) is appreciable: 20.6 g and 7.5 g NaCl dissolve in 100 g EG at 25 [23]. Poly(ethylene glycol) grafted onto solid surfaces is also used to reduce protein adsorption [24].…”
Section: Biochemically Relevant Liquidsmentioning
confidence: 99%
“…This is an example of the 'grafting to' technique. Zhu et al [15] employed a two-step procedure to link the hydroxyl end-group of poly(ethylene oxide) molecules with an ether bond to a silicon surface. Using an even simpler method, Maas et al [16] linked vinyl-terminated polystyrene molecules to a silica surface by letting the vinyl groups react with the hydroxyl groups at a silica surface that appear as a result of the chemisorption of water to form ether bonds.…”
Section: Introductionmentioning
confidence: 99%